Edited by Philippa Glanville and Hilary Young: Elegant Eating. Four Hundred Years of Dining in Style - Davidson, Alan (Petits Propos Culinaires, 2024)
Edited by Philippa Glanville and Hilary Young: Elegant Eating. Four Hundred Years of Dining in Style: V&A Publications, 2002: ISBN 1851773371: 144 pp., h/b, £30.00